Holding Governments Accountable for Service Delivery: The Local Government Councils Scorecard Initiative in Uganda - Tamale, Lillian Muyomba; Cunningham, Kiran (Commonwealth Journal of Local Governance, 2017)
Uganda’s Local Government Councils Scorecard Initiative is a strategic social accountability initiative designed to enable citizens to demand excellence of their local governments and enable local governments to respond to citizen demands for effective and efficient service delivery. Begun in 2009, it is one of the signature programmes of Advocates Coalition for Development and Environment (ACODE), a public policy research and advocacy think tank in Uganda. The initiative is implemented in partnership with the Uganda Local Governments Association. The centrepiece of the initiative is the local government council scorecard, a capacity-building tool for assessing the performance of district-level elected officials in accordance with roles and responsibilities set out in the Uganda’s Local Government Act 1997 (as amended). Incorporating multiple links in the supply and demand chain of good governance and accountability – citizens, civil society organisations, local government and central government – the administration of the scorecard and dissemination of performance results is grounded in an action research methodology. Follow the positive reception of the initiative after eight years of implementation in Uganda, it is hoped that other countries will look to adapt this methodology to engage in similar types of social accountability initiatives.
Keywords: local goverment, service delivery, Uganda